INTERNATIONAL POLITICAL ECONOMY IN THE 21ST CENTURY contemporary issues and analyses. - SMITH, ROY (ROUTLEDGE, 2025)
Understanding the theories that underpin international political economy (IPE), and their practical applications, is crucial to the study of international relations, politics, development and economics. International Political Economy in the 21st Century offers students an engaging and coherent foundation to the subject. It considers traditional and alternative approaches to IPE, and in doing so elucidates key concepts, assumptions and the intellectual and historical context in which they arose and developed. At all times, it makes clear their relevance to issues from trade, finance and government, to environment, technology, health, labour, security, migration, development and culture. The book encourages independent reflection and critical thinking through a range of in-text guiding features. In addition, each chapter presents theoretical analysis alongside contemporary issues, helping the reader to relate to the real world of IPE and to better understand how theory helps inform interpretation of it.This third edition has been comprehensively updated to include: Key coverage of the build-up to and the post-COP26 era; causes and consequences of recent energy crises, and governmental and non-governmental responses to these crises; cryptocurrencies within finance; and the role of 'big data' companies. Fully updated data, reflective questions, recommended readings, concept and example boxes, and illustrations. A new chapter on climate change; and a new chapter on energy and energy security. Online material. This comprehensive and accessible introductory textbook will be key reading for undergraduate students of international political economy.